1990
DOI: 10.1346/ccmn.1990.0380108
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behavior of Na-Montmorillonite Suspensions at Low Electrolyte Concentration

Abstract: Abstract--The prevailing concept that positive-edge to negative-face attraction accounts for the rheological behavior of montmoriUonite suspensions at low electrolyte concentration was investigated. In one experiment, Mg 2+ released from Na-montmorillonite was measured at several NaC1 concentrations; in a second experiment, the viscosity, n, and the extrapolated shear stress, 0, were measured at several clay concentrations, pHs, and NaC! concentrations; and in a third experiment, the absorbance, A, was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…In accordance with Rand et aL (1980), Brandenburg and Lagaly (1988) and Chen et al (1990), the flow behavior of a Na-rich montmorillonite suspension changed significantly in the presence of NaC1 (Figure 1). At a concentration of 10 mEq L -1, the viscosity was lower than that obtained for the clay suspension without free electrolyte for any shear rate (Figures 1 and 2).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…In accordance with Rand et aL (1980), Brandenburg and Lagaly (1988) and Chen et al (1990), the flow behavior of a Na-rich montmorillonite suspension changed significantly in the presence of NaC1 (Figure 1). At a concentration of 10 mEq L -1, the viscosity was lower than that obtained for the clay suspension without free electrolyte for any shear rate (Figures 1 and 2).…”
Section: Resultssupporting
confidence: 88%
“…At low electrolyte concentration in clay suspension, the extended diffuse double layer allows more freedom of movement under stress, whereas at higher electrolyte concentration the attractive forces between clay platelets dominate, and the yield stress and plastic viscosity increase again. Contrary to van Olphen's (1977) hypothesis, Chen et al (1990) suggested that Mg 2+ in octahedral coordination is involved in modifying the rheological properties; Mg 2 § is released from the clay structure by hydrolysis of the clay at low electrolyte concentrations.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…On the other hand, the presence of diff erent types of clay minerals (tosudite, illite, montmorillonite and kaolinite) owing to the feldspar alteration processes which can lead to precipitation of various types of aluminous and alumino-silicate compounds (Guven et al, 1982;Barros, 2000). Th ese types of silicates are composed either residually or primarily and lead to the argillization of granitic rocks producing several types of clay minerals (Zalba, 1982) according to the dominant environmental conditions especially pH values (Dontsova and Bigham, 2005;Chen, 1990) that play an important role both in controlling many chemical reactions and substances solubility (Ollier, 1975). Kaolinite usually develop in an acidic environment or in a neutral environment where intense leaching processes prevail; montmorillonite forms in the presence of certain alkalis and alkaline earths and illite which is the dominant clay mineral in marine sediments (Murray, 1953).…”
Section: Discussionmentioning
confidence: 99%